Integrated Hydrological–Empirical Modeling for Lake Water Balance Estimation in a Data-Scarce Volcanic Catchment - Lintang Nur Fadlillah; Afifudin Afifudin; Firdaus Rakhman Saputra; Sri Utami; Kim Deong Hyeon (Universitas Diponegoro, 2026)
Menjer Lake has undergone various human interventions, such as land use change and hydropower consumption, but has no water level monitoring data in its small catchment area of 2.7 km² and steep morphology. Thus, the objective of this study was to integrate a hydrological model with an empirical model to estimate the water balance of a lake in a data-scarce catchment. The results indicate that the runoff model for an ungauged river demonstrates the good performance of the hydrological model using the Soil and Water Assessment Tool (SWAT) based on its similarity to observed rainfall (R² = 0.93). However, the lake water balance is very complex because of multiple input and output sources. Moreover, land-use change had no significant impact on runoff, as no anomaly was found in the runoff model results. Under existing conditions, artificial inflow plays a significant role in the water balance input and output of Menjer Lake. The artificial inflow covered 76% of the water input, with an outflow of 12.3%, preventing any deficit phase. Overall, this study underscores the importance of considering manual calibration with rainfall data in data-scarce areas. The good correlation between rainfall-runoff shows that this model is also acceptable